Frações da matéria orgânica e estoques de carbono em perfis de solos em pedoformas de região Semiárida - Barbosa, Camila Gonçalves Rodrigues do Nascimento (2020)
The distribution of humic fractions in the soil profile is a way of analyzing the capacity of soils to accumulate organic matter. However, the distribution and accumulation of humic fractions may vary depending on the relief. Thus, in order to evaluate how the variations of the relief influence the organic matter contents of the soil, the objective was to quantify the organic carbon content and the humic fractions in soil profiles of the Semi-Arid region. For that, three soil sequences in slopes with different contours were studied in the experimental station Prof. Ignácio Salcedo, National Semi-Arid Institute (INSA), Campina Grande-PB. In this area, the hyperxerophilous Caatinga vegetation has been preserved over the last 40 years. The soil samples were analyzed for the levels of total organic carbon (TOC) and humic substances (SHs): humic, fulvic and humine in three pedoforms (rectilinear, convex and concave, respectively T1, T2 and T3). Soil TOC levels ranged from 1.62 to 33.24 g kg-1, increasing from the upper third to the lower third in the rectilinear pedoform, with the opposite occurring in the convex and concave, demonstrating that the deposition of materials in the lower parts through erosive processes can be considered efficient for carbon accumulation in the soil in the rectilinear. When analyzing the distribution of COT and SHs content, it was found that through chemical fractionation it was possible to identify that most of the carbon is in the form of humic acids and humine. The degree of humification of organic matter was similar in all Neossols and Planossols studied, with a predominance of humic acid between 39 to 44% of the total organic carbon. The comparison between the straight, convex and concave strands showed that there was a change in the distribution of humic fractions between and within the same strands, demonstrating that changes in organic matter occur on the micro-relief scale.